DEVELOPMENT OF AN INTEGRATED METHOD IN FOREIGN LANGUAGE TEACHING - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
The information presented in our article contributes to the broad and holistic development of children through pedagogical associations and pedagogical and developmental competencies in various subjects in the classroom of the present. In addition, integrated teaching broadens the meaningful concept of foreign language teaching and leads to the formation and development of a wider range of children’s interests, abilities and skills.